Persepsi Masyarakat Terhadap Pemberlakuan Social Distancing Di Masa Pandemi Covid-19 Sebagai Implementasi Modal Sosial - Ade Suherman; Tetep Tetep; Asep Supriyatna; Eldi Mulyana; Triani Widyanti; Opah Saripah; Aneu Rostiani; Lilik Purnawati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
The purpose of this study is to analyze and explain public perceptions of the implementation of social distancing during the pandemic as the implementation of social capital. This study was motivated by the phenomenon of the outbreak of the Covid-19 pandemic in a number of countries, including Indonesia. This condition not only affects the economic condition of a country, hinders social interaction among the community, and also has an impact on the health condition of every human being. To avoid the wider spread of Covid-19, the government was forced to adopt social distancing and physical distancing policies in the form of staying at home, working from home, studying, and worshiping at home. This research approach is descriptive qualitative. The data of this research is the impact of social distancing for the community in Tarogong Kidul District, Garut Regency. Sources of data come from several communities with a total of 50 respondents. Collecting data in this study using interview techniques, record, and continue to take notes. The results of the research can be concluded that with the implementation of social distancing in the pandemic period, at least the community can implement social capital which includes informal values ​​or norms that are shared among members of an interrelated community group, which is based on the values ​​of beliefs, norms and networks social and they respect each other, the development of social capital is the creation of increasingly independent groups of people who are able to participate more meaningfully. Social capital can solve citizens' problems, especially with regard to strengthening friendship, repairing and maintaining public service facilities because it has advantages and is the most appropriate, even though there are other social capital in the community.